2015
DOI: 10.1093/jamia/ocv100
|View full text |Cite|
|
Sign up to set email alerts
|

Serious games for improving knowledge and self-management in young people with chronic conditions: a systematic review and meta-analysis

Abstract: The authors' meta-analysis shows that educational video games can be effective in improving knowledge and self-management in young people with chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
107
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(115 citation statements)
references
References 40 publications
1
107
0
7
Order By: Relevance
“…Clinical applications of patient empowerment using mHealth technologies were described for cancer, diabetes and other chronic medical indications [146-149]. Disease-specific serious games which incorporate choices and engagement show improved self-management behaviors in patients [150-152]. …”
Section: Incentivized Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical applications of patient empowerment using mHealth technologies were described for cancer, diabetes and other chronic medical indications [146-149]. Disease-specific serious games which incorporate choices and engagement show improved self-management behaviors in patients [150-152]. …”
Section: Incentivized Therapiesmentioning
confidence: 99%
“…(A) Self-care consists of disease self-management (patient behaviors related to management and prevention of disease symptoms), self-efficacy and empowerment (perceived abilities to cope with, control and manage disease symptoms). Digital technologies become effective means to deliver empowerment and disease self-management content [148, 150]. (B) Patients activate the habit-forming mechanism by a self-administration of an incentive.…”
Section: Fig (1)mentioning
confidence: 99%
“…Moreover, due to the entertainment aspect, adding serious gaming elements can help to overcome motivational barriers [17]. Serious games have proved effective in improving knowledge and self-management skills in young people with chronic conditions [18], for example, as well as in increasing knowledge about drug and alcohol use in adolescents [19]. Serious games can also have beneficial effects on factors that are considered important for a healthy lifestyle in general such as healthy food choices and physical activity [17].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Systematic reviews have found videogames to be helpful for education and positive reinforcement, resulting in participants' increased knowledge 14 and improved self-management. 15 To our knowledge, although digital game playing has been associated with significant positive effects on physical health outcomes of older adults, 16 no serious digital game has yet been developed to improve HF self-management-related knowledge and behaviors specifically with older adults as the target audience. In this article, we present a Heart Health game prototype-an application for mobile tablets-and we assess the game's usability and evaluate its functionality for improving HF self-management knowledge and behaviors among community-dwelling older adults with HF.…”
mentioning
confidence: 99%
“…Played the game without assistance, n (%) 15 F8, F11) ''HF serious subject.not a game'' (U1) ''Graphics . presented in a fun way'' (F6) ''Would want info from qualified medical persons'' (U7, F6) Reminders Repetitiveness ''Reminders are helpful as you get older and forgetful'' (U6) ''Enjoyed it, been helpful in reminding me.''…”
mentioning
confidence: 99%